The Relevance of the Miranda Rule for the Protection of Human Rights in Law Enforcement in Indonesia - Somomoeljono, Suhardi; Tiara Hardy, Maryzka (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study explores the relevance of the Miranda Rule in protecting human rights within the context of law enforcement in Indonesia. The Miranda Rule, originating from the United States legal system, mandates that individuals taken into custody must be informed of their constitutional rights, including the right to remain silent and the right to legal counsel. Although Indonesia does not formally adopt the Miranda Rule, similar principles are embedded in its legal framework through the constitution and criminal procedure law. This research highlights the gaps in implementation and enforcement that often lead to human rights violations during arrest and interrogation processes. Using a normative legal approach and supported by case analysis, this paper argues that the integration of Miranda-like safeguards in Indonesian law enforcement practices can significantly strengthen the protection of suspects' rights and uphold due process. The study concludes that adopting procedural guarantees akin to the Miranda Rule is not only relevant but essential to aligning Indonesia's legal system with international human rights standards.